MOBILE APPLICATION DEVELOPMENT FOR REGIONAL TRANSPORT OFFICE (RTO) SERVICES USING PYTHON - Vrishti; Dr Basanti Ghanti (International Educational Journal of Science and Engineering, 2026)
Transport management departments handle large amounts of citizen data related to vehicles, driving licenses, and traffic violations. Traditional manual processes for managing these records take a lot of time and are prone to mistakes. This paper outlines the design and development of a mobile application for Regional Transport Office (RTO) services in Karnataka. It is built using Python and the Kivy framework. The application offers role-based access for administrators, officers, and citizens. Users can manage vehicle registrations, view and pay traffic challans, and check the status of their driving licenses. The system features an easy-to-use graphical interface, search and filter options, and real-time payment processing within the app. The application simplifies citizen-facing transport services and shows how Python-based mobile development can effectively enhance e-governance solutions.